Multicultural Values in English Textbook for Senior High School: A Critical Discourse Analysis - Eva Listiani; Bambang Widi Pratolo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research examines the representation of multicultural values ​​in the 12th-grade high school English textbook "Life Today". In the era of globalization, incorporating cultural values ​​into English Language Teaching (ELT) is very important to foster intercultural understanding and tolerance. This research uses qualitative descriptive methods and critical discourse analysis, focusing on visual and verbal content in textbooks. Visual data was analyzed using Barthes' visual semiotic theory, and verbal data was examined using Halliday's systemic functional linguistics and Cortazzi and Jin's cultural components framework. Findings show that the visual content in textbooks represents multicultural values ​​such as Appreciating Other People's Cultural Products (AOPCP), Appreciating Women’s Equal Rights of Women (AWER), and Appreciating Other People's Perspectives (AOPP), with limited representation of Respecting Other People's Traditions (ROPT). Meanwhile, the multicultural value of verbal content in textbooks shows a bias towards universal culture. This study highlights the importance of balanced cultural content in ELT textbooks to improve students' intercultural communicative competence and suggests further research on strategies for teaching multicultural values.